5 UMPSA Senior Lecturers promoted to Associate Professor, Grade DS14 - Siti Sakinah, Mohtar (UMPSA, 2025)
PEKAN, 14 July 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) continues to uphold its commitment to academic excellence with the promotion of five senior lecturers to the position of Associate Professor, Grade DS14, effective from 20 June 2025.